Presynaptic, release‐regulating mGlu2‐preferring and mGlu3‐preferring autoreceptors in CNS: pharmacological profiles and functional roles in demyelinating disease. (3rd March 2016) - Di Prisco, Silvia; Merega, Elisa; Bonfiglio, Tommaso; Olivero, Guendalina; Cervetto, Chiara; Grilli, Massimo; Usai, Cesare; Marchi, Mario; Pittaluga, Anna
Abstract : Background and Purpose: Presynaptic, release‐regulating metabotropic glutamate 2 and 3 (mGlu2/3 ) autoreceptors exist in the CNS. They represent suitable targets for therapeutic approaches to central diseases that are typified by hyperglutamatergicity. The availability of specific ligands able to differentiate between mGlu2 and mGlu3 subunits allows us to further characterize these autoreceptors. In this study we investigated the pharmacological profile of mGlu2/3 receptors in selected CNS regions and evaluated their functions in mice with experimental autoimmune encephalomyelitis (EAE). Experimental Approach: The comparative analysis of presynaptic mGlu2/3 autoreceptors was performed by determining the effect of selective mGlu2/3 receptor agonist(s) and antagonist(s) on the release of [ 3 H]‐d ‐aspartate from cortical and spinal cord synaptosomes in superfusion. In EAE mice, mGlu2/3 autoreceptor‐mediated release functions were investigated and effects of in vivo LY379268 administration on impaired glutamate release examined ex vivo . Key Results: Western blot analysis and confocal microscopy confirmed the presence of presynaptic mGlu2/3 receptor proteins. Cortical synaptosomes possessed LY541850‐sensitive, NAAG‐insensitive autoreceptors having low affinity for LY379268, while LY541850‐insensitive, NAAG‐sensitive autoreceptors with high affinity for LY379268 existed in spinal cord terminals. In EAE mice, mGlu2/3 autoreceptors completely lost their inhibitory activity in cortical, but not in spinal cord synaptosomes. In vivo LY379268 administration restored the glutamate exocytosis capability in spinal cord but not in cortical terminals in EAE mice. Conclusions and Implications: We propose the existence of mGlu2 ‐preferring and mGlu3 ‐preferring autoreceptors in mouse cortex and spinal cord respectively. The mGlu3 ‐preferring autoreceptors could represent a target for new pharmacological approaches for treating demyelinating diseases.